Duchenne muscular dystrophy involves the myocardium and causes arrhythmia: Case report - Liu, Xuhan; Zhao, Wei; Shu, Shangzhi; Zhang, Weihua (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with muscular dystrophy have mutations in the gene that can lead to severe muscle wasting, respiratory issues or heart failure between ages 30 and 40. Currently, there is no effective treatment for DMD-induced heart failure. Case presentation We report a patient with recurrent unexplained fever and muscle soreness was definitelly diagnosed with DMD. An analysis of the patient's genetics revealed a nonsense mutation (C.1207G>T). Hormonal therapy is effective. However, as the disease progresses, the heart structure and function gradually change, and eventually malignant arrhythmias occur. Conclusion We report a rare case of DMD involving the heart causing heart failure and malignant arrhythmia. Currently, no routine treatment is available for these patients, but our treatment regimen may benefit our patient and improve his outcomes. This can also serve as a reference to treat patients with DMD who suffer from heart failure and arrhythmia.